Les inhumés assis laténiens des Pierrières à Batilly-en-Gâtinais (Loiret) - Sophie Liegard; Laure Pecqueur (Gallia)
The preventive excavation of the Pierrières site in Bailly-en-Gâtinais (Loiret) discovered five people buried in a sitting position, from La Tène, allowing for a detailed study. Two of them, being well-preserved, gave us invaluable informations, to feed into the reflection on this unusual and atypical burial custom, testified in different French regions, from Normandy to Charente and as far as Switzerland.